Antihypertensive Therapy Patterns in Prolanis Patients at North Gorontalo City Health Centre, Indonesia - Tuloli, Teti Sutriyati; Reski Manno, Mohamad; Tungadi, Robert; Nurrohwinta Djuwarno, Endah (State University of Gorontalo, 2025)
Hypertension is a chronic condition characterized by persistent elevation of blood pressure above normal limits, which increases morbidity and mortality risk. A systolic blood pressure ≥140 mmHg reflects pressure during cardiac contraction, while a diastolic blood pressure ≥90 mmHg reflects pressure during cardiac relaxation. This study aimed to evaluate the use of antihypertensive drugs in Prolanis patients with persistent hypertension at the North Gorontalo City Health Centre. An observational design was applied using secondary data from medical records of 42 patients who received antihypertensive therapy between January and June 2025. Amlodipine was the most commonly prescribed agent in monotherapy, while combinations of two to five drugs were frequently used. The evaluation revealed that drug selection was appropriate (100%), dosage accuracy was 86%, and adherence to usage rules reached 98%, although some inappropriate dosages and usage instructions were still identified. These findings underscore the need for systematic monitoring, regular prescription audits, strengthened verification processes, laboratory monitoring, and patient education to enhance the safety and effectiveness of hypertension management in primary care.